Neonatal developmental care practice: Current nursing implementation - Siti Yuyun Rahayu Fitri; Sujira Wichaidit; Yani Setiasih; Windy Rakhmawati (Jurnal Keperawatan Padjadjaran, 2024)
The intervention standard of Synactive Development Theory, followed by the Neonatal Integrative Developmental Care Model, has long been recommended as a strategy to lessen the impact of hospitalization on newborns in the NICU. However, it has yet to be widely applied, particularly in developing countries. At least three elements contribute to these developmental care (DC) practices: professional efficacy, nurses' perceptions of developmental care, and a task-oriented organizational culture. Therefore, to improve the DC implementation, it is critical not only to focus on increasing the capacity of personal staff but also to ensure that organizational culture supports DC implementation, with the care unit's managerial staff playing an important role.